2021
DOI: 10.1097/qad.0000000000002738
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of high-sensitivity C-reactive protein, D-dimer, and interleukin-6 levels in multiethnic HIV+ cohorts

Abstract: Objectives: Elevated levels of interleukin-6 (IL-6), D-dimer, and C-reactive protein (hsCRP) are associated with increased incidence of comorbid disease and mortality among people living with HIV (PLWH). Prior studies suggest a genetic basis for these biomarker elevations in the general population. The study objectives are to identify the genetic basis for these biomarkers among PLWH. Methods: Baseline levels of hsCRP, D-dimer, and IL-6, and single nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Multiple processes are theorized to play a role; these include microbial translocation, chronic co-infection with other pathogens such as cytomegalovirus (CMV), host genetics, lifestyle factors (e.g. smoking), side effects of drugs, and persistence of low-level HIV-1 replication that is not 'detectable' via standard clinical assays [14][15][16][17]. We have hypothesized that another potential source of this chronic inflammation may be the persistence, expansion, and biologic activity of replication-incompetent, yet transcriptionally competent 'defective' HIV-1 proviruses [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple processes are theorized to play a role; these include microbial translocation, chronic co-infection with other pathogens such as cytomegalovirus (CMV), host genetics, lifestyle factors (e.g. smoking), side effects of drugs, and persistence of low-level HIV-1 replication that is not 'detectable' via standard clinical assays [14][15][16][17]. We have hypothesized that another potential source of this chronic inflammation may be the persistence, expansion, and biologic activity of replication-incompetent, yet transcriptionally competent 'defective' HIV-1 proviruses [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…In the START trial involving mainly patients from northern countries, sVCAM levels were not found to be associated with the risk of AIDS, serious non‐AIDS events or death [16]. A recently published genome‐wide association multi‐ethnic study showed that in people living with HIV, multiple single nucleotide polymorphisms were associated with levels of high‐sensitivity CRP, D‐dimer and IL‐6 and support the hypothesis that host genetics may partially contribute to chronic inflammation in HIV‐infected individuals [28]. The genetic basis for sVCAM elevations has not been studied so far and may differ according to ethnic origin.…”
Section: Discussionmentioning
confidence: 93%
“…In a multiethnic cohort of patients undergoing antiretroviral treatment for HIV, rs2022309 was associated with increased D-dimer levels (p ¼ 1.9 Â 10 À13 ). 60 Similarly, in the African American cohort in which rs2022030 was studied, rs2022309 was also found to be significantly associated with D-dimer levels (p < 10 À9 ) prior to conditioning on the lead SNP. 59 In a cohort of 2,128 European twins, rs2202309 was also associated with decreased D-dimer levels (β ¼ À 0.24, p ¼ 4.3 Â 10 À8 ); in this study, the SNP was reported to decrease D-dimer levels.…”
Section: D-dimermentioning
confidence: 91%
“…58 Because rs66841827 is an indel rather than a SNP, it was not directly interrogated in and not identified in two larger GWAS of Ddimer. 59,60 Nevertheless, with a minor allele frequency (MAF) of 0.52 in persons of European genetic ancestry, 61 it is unlikely to be very penetrant. rs610277 rs610277 is an A to G intronic polymorphism of F3.…”
Section: Targeted Clinical Investigation Of Human F3 Snpsmentioning
confidence: 99%